Automated Rule-based System for Opitz Feature Recognition and Code Generation from STEP. Issue 3 (3rd May 2016) - Zehtaban, Leila; Roller, Dieter
ABSTRACT: This paper presents a framework for an automatic classification of product shape information aimed for design retrieval and know-how transfer in the design-by-feature using Automated Feature Recognition (AFR) approach. The proposed rule-based method uses an extendable well-known coding system, so called Opitz Coding System applied in Computer Aided Manufacturing (CAM) for grouping part families. The proposed method applies the advantages of know-how transfer between two distinct phases of product development, i.e. CAD and CAM. Many researches already aimed to efficiently integrate computer aided design, analysis and manufacturing for optimizing concepts such as product life cycle and computer aided process planning. However, most of these researches focus on optimization of the downstream process, i.e. from the low-level entities of CAD such as line and points to the high-level manufacturing entities such as chamfers or threads. On the contrary, this paper introduces a new approach for design optimization by considering CAM entities in the first stage of product development. GRAPHICAL ABSTRACT: